Optimization Strategies Applied to Discrete Epidemic Models with Specific Nonlinear Incidence Rate - Amine Bouaine; Mostafa Rachik; Khalid Hattaf (International Journal of Mathematics And its Applications, 2016)
The aim of this paper is to study discrete epidemic models with specific non linear incidence rate, and to investigate, in discrete time, optimal control strategies in which the controls are: vaccination and/or treatment. So, we make use of Pontryagin's maximum principle in order to compare and choose the best medical policy and economical strategy can be adopted and implemented. To end, numerical simulations are carried out to confirm the validity of the models and to prove the performance of the optimization strategies.